Examining The Impact of Digital Story-Based Learning on English Four Skills for Young Learners - Winda Mayasari Pandiangan; Made Hery Santosa; IGA Lokita Purnamika Utami (Publikasi Indonesia, 2024)
Currently, using technology is meaningful and brings lots of changes to our lives as human beings. Especially in the education process, technology has supported the education progress of teachers and students. Combining and applying technology in teaching-learning processes, especially in education technology, has an essential effect on the teaching process. Introduce technology and its part to the students expected to help them improve their ability and support their development. Technology in education, including the digital form, brings the students a new way of fun learning. This study explores the impact of using digital stories in English four skills learning for young learners. The research was obtained by doing a literature review of the impact of digital stories on young learners. A current research study indicates the effects of digital stories on the development of the four English skills of young learners. The current research findings show that digital stories impact students' writing skills, including grammar and ideas or content of written stories.